PENGARUH PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR IPA SISWA KELAS V SD - Hidayad, Fiqri; Kartono, Kartono; Suryani, Suryani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract A problem in this research was â€œhow the influence of the use of a contextual teaching and learning of the results of the learning of the nature of science grade V of public elementary school 11 Pontianak Â ?â€ .This research aims to understand the influence of the use of a contextual teaching and learning of the results of the learning of the nature of science grade V of public elementary school 11 Pontianak. Research methodology used his experiments with the form of eksperimen semu (quasi-experiment) with the design eksperimen Nonequivalent Control Group Design.Population in this research is all students grade V A and V B academic year 2016 / 2017 which consisted of 64 people.Sample in this penelian were students grade 5 which consisted of 50 people consisting of 23 the VB ( class control of ) and 27 the V A ( class eksperimen).Instrument gatherer data of student learning the test results obtained from pre test and post test. The results of the study , obtained the average test results final grade control 70,23 and the average test results final grade 80,61 experiments obtained thitung of 4,168 and ttabel with Î± = 5%percent and dk = 62 as much as , which means thitung (4,168) > ttabel (2,066), thus then Ha accepted .Of recording as effect size (ES), owned valuse 0,99 ( criteria high ) .This means that learning with the use of contextual teaching and learning make a difference that high evaluation learning outcomes from the classroom v of public elementary school 11 Pontianak Â .Â Keyword : Influence, Learning Contextual Teaching and Learning, Study ResultÂ